THE IMPACT AND THE RISK OF ABANDONED BUILDINGS FROM PETROȘANI CITY ON THE URBAN ENVIRONMENT - FAUR, Florin; APOSTU, Izabela-Maria (Studia Universitatis Babeș-Bolyai Ambientum, 2019)
The city of Petroșani, as well as the whole area known as Jiu’s Valley, is integrated in a general vision of transforming a mining region into a tourist destination and, in this context, the aspects related to the quality of the urban landscape must be taken into account in a very serious manner. Although most people, when they hear about landscape, think of the wonderful areas surrounding Petroșani city, the urban landscape should not be ignored either, this being the first that comes in contact with the tourists who will visit this region and will contribute to the economic well-being of the inhabitants. The present paper analyzes the impact of abandoned buildings on the urban landscape (environment) having as a starting point a reality valid in many former industrialized regions, namely that due to the countless restructuring, the population is constantly decreasing and one of the common consequences is represented by the large number of abandoned buildings, in different stages of degradation. These buildings, besides the fact that they strongly degrade the urban landscape (environment), often represent true outbreaks of infection and a real public danger, being exposed to the risk of arson or collapse. For this purpose, we have adapted the methods for identifying/ estimating the anthropic impact on the environment (the network method and the impact/risk matrices) for the situation under study.